PENGABDIAN MASYARAKAT REGENERATIVE PROGRAM: MANGROVE PLANTATION KOLABORASI ECO TOURISM BALI, OPEN FLOW BERSAMA BEM FBA UNMAS DENPASAR - Septa, Ketut; Dharma Manu, Bagus Rama (Fakultas Bahasa Asing, 2023)
This community service activity was organized by Eco Tourism Bali in collaboration with the Open Flow Learning Center and BEM FBA UNMAS Denpasar. This activity is the realization of a sustainable program of activities that aims to give understanding to many people that it is important to protect the environment through planting mangroves. By holding this activity, it is hoped that the wider community, especially the younger generation, will be able to understand the impact that will result if the whole community can preserve nature by planting mangrove trees. This activity was held on February 11 2023 in the Wana Segara Kertih mangrove area, Kedonganan. Provided 700 mangrove seeds along with ± 124 volunteers who are willing to participate in planting mangrove trees. This activity was carried out in two stages or methods, namely mangrove education activities and practice namely planting mangrove trees directly in the Wana Segara Kertih mangrove area. In addition to providing understanding, this activity also aims to preserve and prevent nature from damage that occurs due to natural factors or human activities.